KEMAMPUAN MAHASISWA PGMI DALAM MEMECAHKAN MASALAH GEOMETRI DITINJAU DARI PERBEDAAN KEMAMPUAN MATEMATIKA - Nida Jarmita (Al Khawarizmi, 2019)
This research is an explorative study using qualitative approach that aims to describe the ability of students in solving geometry problems in terms of differences in mathematical skills. Students' problem-solving capabilities were reviewed based on Polya's troubleshooting techniques, namely: understanding the problem, devising a plan, carrying out the plan, and looking back to review the results obtained. The subjects of the study are three students from Department of Primary School Teacher Education (PGMI) of Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Ar-Raniry Banda Aceh. The research process begins by giving a mathematics competency test to the student from a class unit, followed by selecting one student from each group, respectively from high math skills, medium math skills, and low math skills. These three selected subjects were assigned geometry-solving tasks and task-based interviews. The validity of data were checked using time triangulation. The results showed that the subject of high mathematical skill was able to use all 4 steps to solve the problem and provide correct answer. The subject of medium mathematical skill was capable of using the 4 steps of Polya's technique but also was less accurate in giving answers. Subjects of low math skill are able to use only 3 steps but are not correct in giving answers.